HOMOGENIZATION OF TRANSPORT PROCESSES AND HYDRATION PHENOMENA IN FRESH CONCRETE - Beneš , Michal; Beneš , Michal; Štefan , Radek; Štefan , Radek (České vysoké učení technické v Praze, 2020)
The problem of hydration and transport processes in fresh concrete is strongly coupled and non- inear, and therefore, very diﬃcult for a numerical modelling. Physically accurate results can be obtained using ﬁne-scale simulations, which are, however, extremely time consuming. Therefore, there is an interest in developing new physically accurate and computationally eﬀective models. In this paper, a new fully coupled two-scale (meso-macro) homogenization framework for modelling of simultaneous heat transfer, moisture ﬂows, and hydration phenomena in fresh concrete is proposed. A modiﬁed mesoscalemodelisﬁrstintroduced. Inthismodel, concreteisassumedasacompositematerialwithtwo periodically distributed mesoscale components, cement paste and aggregates. A homogenized model is then derived by an upscaling method from the mesoscale model. The coeﬃcients for the homogenized model are obtained from the solution of a periodic cell problem. For solving the periodic cell problem, two approaches are used – a standard ﬁnite element method and a simpliﬁed closed-form approximation taken from literature. The homogenization framework is then implemented in MATLAB environment and ﬁnally employed for illustrative numerical experiments, which verify that the homogenized model provides physically accurate results comparable with the results obtained by the mesoscale model. Moreover, it is veriﬁed that, using the homogenization framework with a closed-form approach to the periodic cell problem, signiﬁcant computational cost savings can be achieved.